ANALISIS FINANSIAL USAHATANI JAMBU BIJI DI KOTA PEKANBARU PROVINSI RIAU - Satria Ahmad Negara; Jum’atri Yusri; Novia Dewi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research to know whether guava farm is worthy for being business in Pekanbaru , to know how long time return of capital who used while to know whether guava farm in Pekanbaru still worthy for being business if there are changes in benefits and costs. Location of the research is purposive in Rumbai and Marpoyan Damai. Data used on this research are Secondary and primary. Primary data obtained from interviews with farmers in region guava Pekanbaru to get technical coefficient data, secondary dataobtainedfrom relevant agencies. Analysis data method was used financial analysis and sensitivity analysis.The result showed of the guava farm for acres 0,6 Ha NPV is Rp .718.515.947, 0.4 Ha NPV is Rp.593.990.733. and0,3 Ha NPV is Rp.487.614.520. Net B/C 0,6 Ha is 6,49, Net B/C 0,4 Ha is6,66. Net B/C 0, 3 Ha is 6,62. NPV value and Net B/C obtained more than 1. IRR value for the acres 0, 6 Ha is 37,4%, IRR 0, 4 Ha is 36,7%, IRR 0, 3 Ha is 35,5% this value bigger than Discount Factor that used 12%. Value of the payback period obtained for acres 0,6 Ha is 3 years 10,5 months, 0,4 Ha is 4 years 2,9 months , 0,3 Ha is 4 years 7 months . Sensitivity analysis by lowering 10% of output prices,production and increasing input prices of the guava was categorized as “feasible” because NPV, Net B / C, IRR are worth positive. Keywords: Feasibility, InvestmentCriteriaAnalysis, Sensitivity Analysis